Immunoglobulin subtypes predict therapy response to the biologics in patients with rheumatoid arthritis - (:unkn) unknown (SPRINGER HEIDELBERG, 2013)
To analyze the effectiveness of rituximab (RTX) versus alternative TNF antagonists (aTNFs) on rheumatoid arthritis (RA) disease activity in different subgroups of patients and relation with extraarticular manifestations of RA and to assess that RF-subsets have potential as predictors of clinical response to RTX. Patients with RA (n = 40, M/F: 3/37) who received aTNFs at least 6 months with good response (group I; n = 20) or discontinued at least one aTNFs because of the ineffectiveness and subsequently received RTX at least one course (group II; n = 20) were retrospectively evaluated. IgM-, IgA-, IgG-rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) levels were measured by ELISA technique. Extraarticular manifestations and radiological scores were also recorded. The mean (SD) age was 51.7 +/- A 6.5 years in group I and 52.1 +/- A 6.1 years in group II patients (p > 0.05). The median disease durations were higher in group II than group I [8.0 (2-30) vs. 13 (3-35) years, respectively, p = 0.04]. Presence of RF [13(61.9 %) vs. 20(100 %) p = 0.001] and extraarticular involvement [5(25 %) vs. 13(65 %) p = 0.01] were higher in group II patients. When Ig-RF subgroups analyzed, all subgroup (IgA, IgM, IgG) levels were higher in group II (p = 0.001, p = 0.05, p = 0.001). IgA-RF levels were significantly high in patients with extraarticular involvement (p = 0.04). Association between high RF levels and having extraarticular manifestations in RA patients may largely be attributed to the IgA isotype.
Keywords: IgA-RF; Rheumatoid arthritis; Rituximab; SERIOUS INFECTIONS; CONTROLLED-TRIAL; DOUBLE-BLIND; RITUXIMAB; METHOTREXATE; EFFICACY; SAFETY; CLASSIFICATION; MALIGNANCIES; ASSOCIATION